Agromorphological Evaluation of Elite Lines of Native Tomato (Solanum lycopersicum L.) from Central and Southern Mexico - María Concepción Valencia-Juárez; Enrique González-Pérez; Salvador Villalobos-Reyes; Carlos Alberto Núñez-Colín; Jaime Canul-Ku; José Luis Anaya-López; Elizabeth Chiquito-Almanza; Ricardo Yáñez-López (Agronomy)
Tomato (Solanum lycopersicum L.) is one of the most important cultivated vegetables in the world. However, in some countries such as Mexico the lack of cultivars adapted to different environmental production conditions is a limitation. Moreover, recent studies have indicated that breeding aimed at increasing yield has led to a loss of genetic diversity. Therefore, it is necessary to explore and characterize new sources of germplasms. This study aimed to characterize new sources of germplasm and identify the most transcendental traits for distinguishing tomato types and lines that are useful for the genetic improvement of the species. Sixty characters were evaluated in 16 advanced lines of native tomatoes from Central and Southern Mexico during the fall–winter cycles 2023–2024 at the Bajío Experimental Station, Celaya, Guanajuato, Mexico, based on the guidelines of the International Union for the Protection of New Varieties of Plants (UPOV) and the International Plant Genetic Resources Institute (IPGRI). The data were analyzed using descriptive statistics, analysis of variance and post hoc tests, canonical discriminant analysis, and the Eigenanalysis selection index method (ESIM). Morphological variation showed that five qualitative traits were determinant factors in distinguishing tomato types and lines, whereas agronomic discriminant traits were the equatorial and polar diameters of the fruit and its ratio, number of locules, pedicel length, stem length, and internode distance. In addition, significant positive correlations were found between leaf length and width, equatorial diameter of the fruit, and polar diameter of the fruit. Lines JCM-17, JMC-10, and JCM-01 were the most selectable lines according to the ESIM values. The morphological variation found and the characteristics with higher selection values identified may be valuable for optimizing the tomato genetic improvement process in general.